2009
DOI: 10.1111/j.1365-2761.2009.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of aquatic mycobacteria in formalin‐fixed, paraffin‐embedded fish tissues

Abstract: The isolation of mycobacteria from field samples is problematic, and isolation of the bacterium is sometimes not even attempted. The detection of mycobacteria through traditional histology using formalin-fixed, paraffin-embedded (FFPE) tissues is neither sensitive nor specific. However, detection of mycobacterial DNA from FFPE specimens, suspected of being infected with mammalian mycobacteriosis, is a routine clinical procedure. In the present study, a polymerase chain reaction (PCR)-based method was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“…There could be a variety of reasons why FFPE samples can give false negative readings by real-time RT-PCR. In fact, in most studies that examine FFPE samples, the effects of temperature and time of tissue handling, processing and storage of tissues in formalin may reduce the sensitivity of RT-PCR as well as have a tendency to degrade RNA or DNA, which can result in short fragments and low copies of genetic material (Fiallo et al 1992, Foss et al 1994, Bhudevi & Weinstock 2003, Bhatnagar et al 2007, Pourahmad et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…There could be a variety of reasons why FFPE samples can give false negative readings by real-time RT-PCR. In fact, in most studies that examine FFPE samples, the effects of temperature and time of tissue handling, processing and storage of tissues in formalin may reduce the sensitivity of RT-PCR as well as have a tendency to degrade RNA or DNA, which can result in short fragments and low copies of genetic material (Fiallo et al 1992, Foss et al 1994, Bhudevi & Weinstock 2003, Bhatnagar et al 2007, Pourahmad et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…PCR confirmation and species identification of mycobacteria from histological sections are less optimal but can be done (Jacobs et al 2009a; Loeschke et al 2005; Pourahmad et al 2009; Zerihun et al 2011). In fixed specimens, the duration of fixation, method of decalcification, and thickness of sections all influence the successful detection of mycobacteria by PCR.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Of the over 150 cases diagnosed by histology by ZIRC, identification of the bacteria to the species level using culture or molecular methods has been achieved on less than 20 cases (Watral and Kent 2007, Whipps et al 2007, 2008, 2012). Several studies have previously demonstrated that mycobacterial DNA can be amplified from human and animal (including fish) tissues from paraffin blocks (Ghossein et al 1992, Miller et al 1997, Marchetti et al 1998, Zink and Nerlich 2004, Pourahmad et al 2009a). Efforts to develop more reliable PCR assays that would reduce the time required for diagnosis as well as increase both the specificity and sensitivity of detecting mycobacteria in formalin-fixed, paraffin-embedded (FFPE) tissues have been ongoing, and are mostly focused on human mycobacteriosis (Pao et al 1988, Pao et al 1990, Fiallo et al 1992, Hardman et al 1996, Rish et al 1996, Osaki et al 1997, Salian et al 1998, Whittington et al 1999, Li et al 2000, Singh et al 2000, Baba et al 2008) and to a lesser extent, mycobacteria infections of animals including fish (Gyimesi et al 1999, Puttinaowarat et al 2002, Pourahmad 2009 a,b, Zerihun et al 2011).…”
Section: Introductionmentioning
confidence: 99%